Bor'ba za ustanovlenie i upročenie sovetskoj vlasti. Chronika sobytij. 26 oktjabrja 1917 g. - 10 janvarja 1918 g. [Pod red. I.G. Dykova, L.S. Gaponenko, G.N. Golikova i dr. Sost. L.M. Gavrilov, V.V. Farsobin, R.G. Cypkina] (Izd-vo Akad. nauk SSSR, 1962)
S ukaz-mi.